2012
DOI: 10.1007/jhep07(2012)126
|View full text |Cite
|
Sign up to set email alerts
|

Excited and exotic charmonium spectroscopy from lattice QCD

Abstract: We present a spectrum of highly excited charmonium mesons up to around 4.5 GeV calculated using dynamical lattice QCD. Employing novel computational techniques and the variational method with a large basis of carefully constructed operators, we extract and reliably identify the continuum spin of an extensive set of excited states, states with exotic quantum numbers (0+-, 1-+, 2+-) and states with high spin. Calculations are performed on two lattice volumes with pion mass approximately 400 MeV and the mass dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
233
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 240 publications
(265 citation statements)
references
References 73 publications
(214 reference statements)
31
233
1
Order By: Relevance
“…refs. [34,35], does not lead to any improvement of the signal for the state η (2S). With the statistical quality of our data more operators included in GEVP would not help improving the extraction of higher excited states either.…”
Section: Jhep05(2015)014mentioning
confidence: 91%
“…refs. [34,35], does not lead to any improvement of the signal for the state η (2S). With the statistical quality of our data more operators included in GEVP would not help improving the extraction of higher excited states either.…”
Section: Jhep05(2015)014mentioning
confidence: 91%
“…In Ref. [607] the Hadron Spectrum Collaboration studied the highly excited charmonium mesons up to around 4.5 GeV using dynamical QCD configurations. They found that the D-wave 2 −+ charmonium state is around 30 MeV below the X(3872), while the first radial excitation of the P-wave 1 ++ state is around 110 MeV above the X(3872).…”
Section: Lattice Qcdmentioning
confidence: 99%
“…[607], Liu et al presented a mass spectrum of the highly excited charmonium mesons and the charmonium hybrid mesons using dynamical lattice QCD simulation. They used the operator of the general formψΓ The mass spectra of heavy quarkonium hybrids were also studied in Coulomb gauge QCD with gluon degrees of freedom in the mean field approximation in Ref.…”
Section: The Hybrid Charmoniummentioning
confidence: 99%
“…The same action is used for valence charm quarks as for the light and strange quarks (with tadpole-improved tree-level clover coefficients), where the charm quark mass parameter has previously been tuned using the physical η c mass [43]. By fitting to a relativistic dispersion relation, the anisotropy measured from the D-meson has been determined to be ξ D = 3.454(6) [34], which agrees with the value measured from the pion ξ π = 3.444 (6) [44].…”
Section: Calculation Detailsmentioning
confidence: 99%